Educação em ciências naturais para estudantes com surdocegueira : uma análise no contexto de uma escola de surdos - Perassolo, Valquíria (2018)
The school inclusion of people who are at the margins of educational systems is one of the great challenges of Brazilian education. In the named knowledge society the number of people excluded from the right of access to schooling is great. The issue is even more complex and challenging when it comes to people with disabilities, in particular cognitive aspects. We start from the perspective that wheelchair users, people with visual impairments, deaf people, deafblind people and people with rare genetic syndromes need differentiated attention. This research project discuss the education of children, adolescents and young people with deafblindness, who are socially invisible. The main objective is to analyze Natural Sciences Education for students with deafblindness in the context of a school for the education of the deaf. The theoretical framework is anchored in authors who study and research this theme. In methodological terms this research is guided by the qualitative approach of the type case study. The empirical material for the development of the analyzes was extracted from academic productions that discuss the theme, texts of current educational legislation and participant classroom observation aimed at the education of students with deafblindness. As a result of the research we can discourse that in the period considered, Natural Sciences Education was related to the following themes: sense organs (since these sensory mechanisms must be stimulated in order that the subject with deafblindness notes himself in the world); personal hygiene care and the materials used on everyday life (aiming at an autonomy of daily life); notions of plant and animal diversity. This study is expected to potentiate debates on inclusion policies and science socialization in our days, especially for people with deafblindness who have been historically marginalized from the school context.